+0  
 
0
24
2
avatar+181 

What is the y- intercept of the exponential function?

 

f(x) = -32 (2)^[x-3] + 3

 

y intercept = ?

whosmans  Oct 31, 2018
 #1
avatar+13567 
0

Y-intercept occurs where x = 0

   Substitute x=0 in to the equation to find the y-intercept value....

ElectricPavlov  Oct 31, 2018
 #2
avatar+90968 
+2

-32 (2) ^(x - 3) + 3

 

Let x  =  0

 

-32 (2)^(0 - 3) + 3

 

-32 (2)^(-3)  + 3

 

-32 / (2)^3  + 3

 

-32 / 8  + 3

 

-4 + 3  =

 

-1   =  y intercept

 

 

cool cool cool

CPhill  Oct 31, 2018

38 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.